Drought resistance characters among four rice varieties - a review / Ahmad Zahrul Azri and Shamsiah Abdullah - Azri, Ahmad Zahrul; Abdullah, Shamsiah (Faculty of Plantation and Agrotechnology, 2018)
Rice Oryza sativa is one of the most important crops in the world. In Malaysia, rice one of the most planted crops and it is considered as commodity. Most Malaysian consume rice on a daily basis. However, the rice production in Malaysia is produced by the cultivation of lowland rice varieties especially in Peninsular Malaysia. Drought is one of the major issue faced by the rice industry. It happens as the result of natural phenomenon such as El Nino and human activities. For rice, drought will cause a lot of disturbance especially on the growth, development and yield performance. Some rice varieties have developed adaptation characteristics to fight the drought and water stress phenomenon. These characteristics include the change in morphological, physiological and biochemical responses. This review focused on the potential rice varieties in Malaysia that possessed the drought tolerance characteristics. This review also discussed rice plant responses towards drought condition among the selected varieties. Malaysian rice varieties were selected in this review1. Those varieties namely MR211, MR219 and two mutant lines of MR219 which are MR219-4 and MR219-9 are selected and is included in this review. MR219-4 and MR219-9 were identified as high-yielding drought-tolerant genotypes as they maintained good performance under drought stress condition for all the measured traits compared to other varieties, MR211 and MR219. but MR219-4 showed better result between those two mutant lines. Besides the adaptations and responses of rice plant on drought, this review also discussed on the strategy such as mitigation measures for countering drought in the future.